The Effect of Procedural Justice, Distributive Justice, Job Satisfaction and Organizational Commitment to Organizational Citizenship Behavior in Pariaman, West Sumatera, Indonesia - Diane Mary; Hilda Mary; Ronny Andri Wijaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2016)
Procedural justice, distributive justice, job satisfaction and organizasional commitmen has proven influence the incidence of extra-role behavior in a public organization. This research presents the correlation of procedural justice, distributive justice, job satisfacion, and organization’s commitment to organizational citizenship behavior variables. The population in this research directly sampled with a total 71 peoples ranging from leaders to the staff level within the Region Secretary of Pariaman. The research method is quantitative with data collection through questionnaire. Furthermore, the data obtained were processed using SPSS version 17. From the analysis, we can conclude that there are positive and significant effects of procedural justice and organizational commitment on organizational citizenship behavior on Regional Secretariat of Pariaman. The results showed that the independent variables of the political perception of 59,7%, the balance of 40,3% determined by other variables that not studied. Suggestions that writers can conveys, in order to enhance distributive justice, procedural justice, job satisfaction and organizational commitment can be acquired through commitment, consistency, intense communication, discussion, work culture, performance and reward; and it also necessary to develop and increase self-employees through formal education, technical training, structural and functional, seminars, discussions, lectures, and procurement of books relating to the implementation of tasks in order to achieve its objectives effectively and efficiently.